PET Image Quality Evaluation at Upper and Lower Threshold of ¹⁸F-FDG dose: A Pilot Study in Vietnamese Patients - Nguyen, Thai Ha; Duong, Trong Luong; Nguyen, Thanh Trung; Nguyen, Thu Van (Old Journal, 2018)
¹⁸F-FDG Positron Emission Tomography (PET) is the most common modality used in cancer diagnosis and monitoring. PET imaging results in patients being exposed to a certain level of radiation, which may be harmful to the body. Research has been conducted on reducing radiation dose in PET imaging in order to minimize radiation risks, at the same time still maintaining diagnostic image quality. This study was a pilot study conducted at the 108 Government Military Hospital in Hanoi, Vietnam, whereby randomly selected patients regardless of body weight were sent for whole body ¹⁸F-FDG PET imaging with a dose of 0.1 mCi/kg, which is the lower threshold in the recommended dose range in the guidelines on the Society of Nuclear Medicine and Molecular Imaging website. Another group of patients underwent the same PET procedure with dose calculation using the upper threshold of the same range (0.15 mCi/kg). Image quality, manifested through the Signal-to-Noise Ratio (SNR), was compared between the low-dose and high-dose groups. No statistically significant difference in image quality was revealed between the two groups, suggesting that dose reduction in a certain limit did not affect PET image quality.